Analisis Service Dominant Logic Komunikasi Manusia vs Chatbot di Angkasa Pura Bandara Adi Soemarmo - Sulistya, Gladys Berlian; Pinem, Yune Andryani (LPPM STT Terpadu Nurul Fikri, 2025)
This study analyses Service Dominant Logic (SDL) in the context of services at Angkasa Pura Adi Soemarmo Airport by comparing human-based and Chatbot-based communication. The urgency of this research stems from the increasing adoption of digital technologies such as Chatbots in information service, which potentially shifts the dynamics of interaction and influences passenger satisfaction. A mismatch between customer expectations and service experience—whether delivered by humans or Chatbots—may impact airport business processes, including operational efficiency, time management, and customer loyalty. This research employs a quantitative method with a population of airport passengers from 2016 to 2023 and a sample of 100 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using descriptive statistics and Chi-square tests via SPSS. The results show that human communication scored highest in the value co-creation dimension with 1754 points, while Chatbots performed best in the service exchange dimension with 865 points. The Chi-square test indicates a significant relationship between the two types of communication (p < 0.05). These findings suggest that strategic integration of human and Chatbot communication is essential to enhance passenger satisfaction and optimize service efficiency in the air transport sector.